Antisipasi Penanganan Masalah pada Praktek Keinsinyuran untuk Pekerjaan Penanganan Longsoran dengan Menggunakan Bore Pile - Lapadengan, Tania; Sangkertadi; Pandey, Sisca V (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
In engineering practice, various methods have been implemented to stabilize landslide-prone slopes, one of which is the use of bore piles. Bore piles are structures that hold back soil and make slopes more stable by reinforcing the ground inside them. However, the application of bore piles in landslide mitigation presents its own challenges, making it essential to identify and anticipate potential issues that may arise in field engineering practice. Bore piles are installed vertically, either parallel or staggered, at specific spacing and are often combined with capping beams and struts to resist soil movement and provide lateral restraint. This method is commonly applied to high-risk slopes or critical infrastructures such as roads, bridges, and buildings. Anticipation strategies in engineering practice consist of three stages: planning, implementation, and long-term maintenance, with this study focusing specifically on anticipation strategies during the implementation stage. Although bore piles serve as an effective solution to reduce landslide risk, their success depends heavily on proper planning, construction execution, and maintenance. Issues such as soil conditions, construction quality, and external factors must be addressed through a comprehensive engineering approach.